Rainfalls sprinkle cloud bacterial diversity while scavenging biomass. Issue 11 (3rd November 2021) - Péguilhan, Raphaëlle; Besaury, Ludovic; Rossi, Florent; Enault, François; Baray, Jean-Luc; Deguillaume, Laurent; Amato, Pierre
ABSTRACT: Bacteria circulate in the atmosphere, through clouds and precipitation to surface ecosystems. Here, we conducted a coordinated study of bacteria assemblages in clouds and precipitation at two sites distant of ∼800 m in elevation in a rural vegetated area around puy de Dôme Mountain, France, and analysed them in regard to meteorological, chemical and air masses' history data. In both clouds and precipitation, bacteria generally associated with vegetation or soil dominated. Elevated ATP-to-cell ratio in clouds compared with precipitation suggested a higher proportion of viable cells and/or specific biological processes. The increase of bacterial cell concentration from clouds to precipitation indicated strong below-cloud scavenging. Using ions as tracers, we derive that 0.2 to 25.5% of the 1.1 × 10 7 to 6.6 × 10 8 bacteria cell/m 2 /h 1 deposited with precipitation originated from the source clouds. Yet, the relative species richness decreased with the proportion of inputs from clouds, pointing them as sources of distant microbial diversity. Biodiversity profiles, thus, differed between clouds and precipitation in relation with distant/local influencing sources, and potentially with bacterial phenotypic traits. Notably Undibacterium, Bacillus and Staphylococcus were more represented in clouds, while epiphytic bacteria such as Massilia, Sphingomonas, Rhodococcus and Pseudomonas were enriched in precipitation. Abstract : Comparative study of bacterial diversity in clouds and precipitation reveals distinct structures indicative of bacteria distribution and dispersal in the outdoor atmosphere.